Pengaruh E-service Quality Terhadap Keputusan Pengguna Jasa Ojek Online Go-Ride dalam Aplikasi Go-Jek melalui Kepercayaan Konsumen di Kota Jambi - Ihsan, Mohammad; Siregar, Ade Perdana (Universitas Batanghari, 2019)
The purpose of this study was to identify the effect of e-service quality on consumer trust in Go-Ride online motorcycle taxi users in the Go-Jek application in Jambi City. identify the influence between e-service quality and consumer trust in the decisions of Go-Ride online motorcycle taxi users in the Go-Jek application in Jambi City and identify the influence of e-service quality on Go-Ride motorcycle taxi users' decisions on the Go-Jek application through consumer trust in Jambi City. The population of this study was the people of Jambi city while the sample was the people of Jambi city who more than once used the Go-Jek service as many as 150 people. The data method uses path analysis. The results of the study revealed that e-service quality had a significant influence on consumer trust in Go-Ride online motorcycle taxi users in the Go-Jek application in Jambi City, e-service quality and consumer trust had a significant influence on Go-ojek online motorcycle users' decisions. Ride on the Go-Jek application in Jambi City and e-service quality had a significant influence on consumer trust in Go-Ride online motorcycle taxi users in the Go-Jek application through consumer trust in Jambi City